P2.054 Optimal Processing of Chlamydia Trachomatis Simulated Samples from Proficiency Testing Panels by Dilution with Cobas© PCR Media. (13th July 2013) - Engstrom-Melnyk, J; Rodriguez, P; Liesenfeld, O; Osiecki, J
Abstract : Background: Proficiency materials are designed to resemble true clinical samples, yet challenges exist in procuring sufficient quantity of patient material. Simulated samples are often provided for this testing. Matrix effect with simulated samples can confound molecular assessment, having negative consequences for the laboratory through failed proficiency testing. This study was conducted to evaluate simulated urine samples provided for proficiency testing which generate invalid results with the cobas © CT/NG test. Methods: Simulated urine proficiency panels were acquired from a commercial proficiency testing provider. Panels were evaluated in triplicate by routine procedure at neat concentrations and processed with cobas © PCR media at the following dilutions 1:1, 1:5, 1:10, 1:20, 1:50, 1:100, 1:200, and 1:500. The samples were held at room temperature (1 complete set) for 1 hour prior to loading on the cobas © 4800 system, while the second complete set of samples were processed 24 hours later. Samples were tested using two different cobas © 4800 workflows (400ul vs. 850ul of sample). Internal control and target Ct values were assessed for each sample to determine success of amplification. Results: Invalid results due to internal control failures were observed at neat concentrations of simulated urine samples. Incubation of samples for 1 hour or 24 hours in cobas © PCR media, showed no significant difference between target and IC Ct values indicating incubation period in cobas © PCR media does not impact performance. Simulated Urine Sample dilution of 1:5 in cobas © PCR media using the 400ul sample input volume produced similar IC Ct values (mean Ct = 35.5) to cobas © PCR media tested alone (mean Ct = 36), and produced a robust target signal (mean Ct = 22). Conclusions: Proficiency testing materials may require optimization for use on commercially available systems. Optimal processing of simulated urine specimens can be achieved by dilution in cobas © PCR media.